2014
DOI: 10.1016/j.jinteco.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Openness and optimal monetary policy

Abstract: 4Non-technical summary 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 52 publications
0
16
1
2
Order By: Relevance
“…For example, for a given level of exports and imports, greater global competition at each stage of production would result in more substitutability of factor inputs and outputs and hence raise the influence of global slack conditions at the expense of domestic ones. In this sense, trends in intermediate trade may be more informative about trends in global competition than the conventional measure based on the sum of all exports and imports (Lombardo and Ravenna (2014) and Burstein et al (2008)). 8…”
Section: Growth Of Gvcs Over Time (In Per Cent)mentioning
confidence: 99%
“…For example, for a given level of exports and imports, greater global competition at each stage of production would result in more substitutability of factor inputs and outputs and hence raise the influence of global slack conditions at the expense of domestic ones. In this sense, trends in intermediate trade may be more informative about trends in global competition than the conventional measure based on the sum of all exports and imports (Lombardo and Ravenna (2014) and Burstein et al (2008)). 8…”
Section: Growth Of Gvcs Over Time (In Per Cent)mentioning
confidence: 99%
“…En estimant les déterminants des exportations bilatérales, ils montrent que l'effet positif et significatif de l'intégration monétaire sur le commerce bilatéral est affaibli par la complexité des régimes politiques. D'autres études ont privilégié l'effet de politiques monétaires optimales sur le commerce (Lombardo et Ravenna, ; Cooke, ; Gong et al ., ).…”
Section: Revue Sélective De La Littérature Récenteunclassified
“…On the one hand, Clarida, Galí, and Gertler (2002) and Corsetti, Dedola, and Leduc (2010) show that in a specific class of economic models the design of monetary policy in open economies is "isomorphic" to the conduct of monetary policy in a closed economy: Central banks should only respond to changes in inflation and the output gap, but they may respond differently to these depending on the degree of trade openness. On the other hand, morerecent studies have shown that this need not necessarily be the case in more realistic environments (Faia and Monacelli, 2008, De Paoli, 2009, and Lombardo and Ravenna, 2014 in which central banks in open economies may also want to respond to changes in other variables such as the real exchange rate.…”
Section: Introductionmentioning
confidence: 99%